Lupus nephritis kidney biopsy characteristics and preterm birth - Reynolds, Monica L.; Gibson, Keisha L.; Manuck, Tracy A.; Poulton, Caroline J.; Blazek, Lauren; Stuebe, Alison M.; Hogan, Susan L.; Falk, Ronald J.; Derebail, Vimal K. (Frontiers in Nephrology, 2024)
Individuals with lupus nephritis (LN) are at high risk of adverse maternal and fetal outcomes in pregnancy. Outside of pregnancy, proliferative lesions on kidney biopsies are associated with disease progression, but these have not been consistently associated with increased risk in pregnancy. This retrospective, single-center study examines how histologic findings, the timing from kidney biopsy to pregnancy, and the clinical features in the first trimester are associated with preterm birth among individuals with LN. Among 35 deliveries in 31 women, the mean gestational age at delivery was 33.8 weeks. The presence of a urine protein-to-creatinine ratio >0.5 g/g in the first trimester was associated with preterm delivery (81% vs. 36%, p = 0.04). Preterm birth was more common in individuals with glomerular crescents on biopsy (89% in those with >20% crescents vs. 50% in those with <20%, p = 0.06). A pregnancy occurring within 2 years after a kidney biopsy was more likely to result in preterm birth than if the biopsy was performed more than 2 years prior to conception (82% vs. 23%, p = 0.01). The time from diagnostic biopsy may be a surrogate for disease activity, and a 2-year delay from biopsy might allow sufficient time to achieve disease remission. Overall, these data could aid family planning discussions and promote preconception disease optimization for patients and their providers.